Estudo DFT dos antibióticos rifampicina e claritromicina e de suas dispersões sólidas - BARROS, Ranna de Sousa (2022)
A solid dispersion of a drug is a material formed from drug-drug, drug-coformer or amorphous drug-polymeric matrix interaction, presenting physical properties and chemical characteristics. Thus, the preparation of a solid dispersion of a drug can contribute to increase the solubility and bioavailability of drugs with low water solubility, such as the leprosy drugs rifampicin (RIF) and clarithromycin (CLA). In this work, a theoretical study of the properties of the drugs RIF and CLA, of the coformers tromethamine (TRIS) and oxalic acid (OXA), as well as of the RIF-TRIS and CLA-OXA systems, in the formation of solid dispersions, from computational calculations using functional DFT (Density Functional Theory). The DFT is widely used in the study of properties of multielectronic systems, considering the electronic density as a fundamental parameter. With a relatively low computational cost, the DFT enables the determination of different properties of drugs, as well as the study of solid dispersions. Thus, DFT was used to investigate the intermolecular interactions between RIF and TRIS, as well as between CLA1+ and OXA1- , which occur in the formation of the studied solid dispersions. To this end, a theoretical study of the RIF and its interaction with TRIS, as well as the CLA1+ ion and its interaction with the OXA1- ion, was carried out with the Gaussian software16, using the DFT functional ωB97X-D and the set of base functions 6-31G(d). The solvation effect in methanol was studied using the IEFCM continuous solvation method. The optimized geometry of each of the systems was obtained and each of them was confirmed as corresponding to a minimum on the potential energy surface, from vibrational frequency calculations, with all vibrational frequencies positive. Thermodynamic properties, electrostatic potential maps, molecular orbitals, partial atomic charges, dipole moment vectors and theoretical infrared and Raman spectra were obtained, contributing to a more detailed study of the interactions and to the characterization of the studied systems. The Gibbs free energy change in vacuum associated with the interaction in the RIF-TRIS heterodimer is -39.73 kcal/mol, while in the CLA-OXA heterodimer it is -5.67 kcal/mol, and in the CLA1+ -OXA1- heterodimer is -102.01 kcal/mol, these being the most favorable interactions found. In the theoretical study, the occurrence of hydrogen bonding was verified in the three heterodimers studied (RIF-TRIS, CLA-OXA and CLA1+ -OXA1- ). In the RIF-TRIS heterodimer, there is an interaction between the atoms of H17 from TRIS with O28 from RIF, as well as between O1 from TRIS with H41 from RIF, with a distance between atoms of 1.65 Å in the interaction H17∙∙∙O28 and 1.68 Å in the O1∙∙∙H41 interaction, with angles of 171.93° O- H∙∙∙O and 165.41° O-H∙∙∙O, in vacuum. In the CLA-OXA heterodimer, the interaction occurred between the atoms H128 of OXA and O23 of CLA in vacuum, with the distance between the O and H atoms of 1.75 Å and the O-H∙∙∙O angle of 158.61o. For the CLA1+ - OXA1- heterodimer, the interaction takes place between the H70 atoms of CLA1+ with the O15 of OXA1- , with a distance between the atoms of 1.66 Å with the angle H-O∙∙∙N of 155.88° for the CLA1+ -OXA1- heterodimer in vacuo. Non-covalent interactions (NCI) studies with the Multiwfn program also confirmed the occurrence of the described hydrogen bonds. These parameters were obtained from the most favorable interactions in vacuum, confirming the contribution of these stabilizing interactions in the formation of solid dispersions of RIF and CLA drugs.